Advancements in the Structural Design and Analysis of Water Intake Wells: A Comprehensive Review - Divyanshu Jhadane; Dr. Abhay Kumar Jha (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Water intake wells are critical components of water treatment infrastructure, requiring robust structural design to withstand complex loading conditions, including seismic, hydraulic, and geotechnical forces. This paper presents a comprehensive review of advancements in the design and analysis of intake well structures, focusing on key performance parameters, optimization strategies, and emerging technologies. The study evaluates various modeling approaches, including finite element analysis (FEA) using software such as STAAD.Pro and ANSYS, to assess structural behavior under different load scenarios. Key findings highlight the superior performance of variable wall thickness designs over conventional uniform thickness configurations, demonstrating significant improvements in material efficiency and structural resilience. Emerging technologies such as smart materials, digital twins, and machine learning-based optimization are explored for their potential to enhance durability and sustainability. The review also identifies critical challenges in current design practices, including limitations in seismic analysis methods and the need for improved lifecycle assessment frameworks. Practical recommendations are provided for engineers and policymakers to adopt performance-based design approaches and integrate sustainable materials in future projects. This paper serves as a valuable resource for researchers and practitioners aiming to advance the state-of-the-art in water intake well design, ensuring safer, more efficient, and environmentally responsible infrastructure.